High performance protonic ceramic fuel cell systems for distributed power generation. (15th November 2021) - Ferguson, Kyle; Dubois, Alexis; Albrecht, Kevin; Braun, Robert J.
Highlights: A summary of PCFC state-of-the-art performance and development progress is given. An overview of protonic ceramic fuel cell operational characteristics and intrinsic advantages is provided. PCFC system concepts with net system electric efficiencies approaching 70% are presented. The effects of different system configurations and parameter selection on performance are quantified. Cost and performance benefits of PCFCs are summarized and compared to other fuel cell technologies. Abstract: The technology landscape around distributed generation continues to evolve in response to increasing demand for high-efficiency, low-emission, low-cost power generation. While emerging distributed power technologies, such as solid oxide fuel cells (SOFCs), continue to advance, they still face challenges due to their high capital costs, and shorter lifetimes that typically arise from electrochemical stack performance degradation at high operating temperatures (>750 °C). Recent advancements in protonic ceramic fuel cells (PCFCs) offer the potential to mitigate drawbacks of their higher temperature SOFC counterparts by enabling lower operating temperatures (550 °C–600 °C) with acceptable power densities. The present work leverages the recent progress in protonic ceramic cell and stack technology development to generate viable system configurations and evaluate the energetic performance potential of PCFC-based systems for stationary power generation. Process system engineering of two water-neutral system concepts, which provide 25 kW of electric power and process hot water, are presented and evaluated through sensitivity studies. Stack design parameters are altered and used to gauge the effect on system performance characteristics, including fuel cell stack and balance-of-plant sizing requirements, and electric and cogeneration efficiencies. The study finds that the potentially high per-pass fuel utilization capability of PCFC stacks could enable unprecedented electric efficiencies approaching 70% without hybridization with other prime movers.